Potential Exploration of Biocompatible Carbon-Coated MoSe2 Nanoparticles for Exploration of the Photothermal Potential in the Treatment of Human Choriocarcinoma - Yu H; He X; Yao J; Gu X; Zhou L; Gao L; Wang J (International Journal of Nanomedicine, 2024)
Hui Yu,1 Xinyi He,1 Jinmeng Yao,1 Xiaoya Gu,1 Lin Zhou,1 Li Gao,1,2 Jia Wang1 1Department of Obstetrics and Gynecology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Health Science Center, Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of ChinaCorrespondence: Jia Wang; Li Gao, Email wangjia_80@163.com; gaoli23@mail.xjtu.edu.cnBackground: Molybdenum diselenide (MoSe2), as a nano near-infrared absorber, has been widely studied in the field of photothermal therapy of cancer. However, there is little research on its application in the treatment of human choriocarcinoma.Methods and Results: In this paper, a new type of carbon-coated MoSe2 (MEC) nanoparticles was prepared by a one-step hydrothermal method. The chemical characterization including SEM, TEM, EDS, XRD, FT-IR, TGA, Roman, and XPS showed that MEC was successfully synthesized. MEC exhibited a high photothermal conversion efficiency (50.97%) and extraordinary photothermal stability under laser irradiation. The cell experiment results showed that MEC had good biocompatibility on normal cells while significant photothermal effect on human choriocarcinoma (JEG-3) cells, achieving a good anticancer effect. The level of reactive oxygen species (ROS) in JEG-3 cells was significantly increased under the combination of MEC nanoparticles and near-infrared radiation. MEC nanoparticles could induce apoptosis of JEG-3 cells in combination with near-infrared radiation. Finally, transcriptomic analysis verified that MEC combined with laser radiation could inhibit DNA replication and induce apoptosis, thus improving its therapeutic effect on human choriocarcinoma.Conclusion: MEC nanoparticles exert an excellent photothermal effect and may become an important candidate drug for the treatment of human choriocarcinoma.Keywords: MoSe2, carbon-coated, biocompatibility, human choriocarcinoma, photothermal therapy